2000
DOI: 10.1046/j.1525-1594.2000.06557-3.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrolyzed Water on Wound Healing

Abstract: Electrolyzed water accelerated the healing of full-thickness cutaneous wounds in rats, but only anode chamber water (acid pH or neutralized) was effective. Hypochlorous acid (HOCl), also produced by electrolysis, was ineffective, suggesting that these types of electrolyzed water enhance wound healing by a mechanism unrelated to the well-known antibacterial action of HOCl. One possibility is that reactive oxygen species, shown to be electron spin resonance spectra present in anode chamber water, might trigger e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 8 publications
1
37
0
3
Order By: Relevance
“…SOW does not cause harmful effect on the human tissues and used for various conditions like wound, skin infections, ulcers and diabetic foot (2,3). The other forms of this formulation were not neutral pH and has a strong acid aqueous ingredient and theoretically may lead to toxic and negative effect on the tissue and subcellular level (4).…”
Section: Introductionmentioning
confidence: 99%
“…SOW does not cause harmful effect on the human tissues and used for various conditions like wound, skin infections, ulcers and diabetic foot (2,3). The other forms of this formulation were not neutral pH and has a strong acid aqueous ingredient and theoretically may lead to toxic and negative effect on the tissue and subcellular level (4).…”
Section: Introductionmentioning
confidence: 99%
“…Its application has been investigated in medical [13][14][15][16][17], dental, animal husbandry, horticulture, restaurant and other areas where microbial growths are known to present potential health threats [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…12) Another study testing different waters concluded that the wound healing effect may be due to the free radicals, and the other in vivo study proposed that acidic water enhances epithelialization, collagen deposition and increase of inflammatory cells. 15,16) Despite these studies in relation to wound healing, the exact mechanism of the healing effect is still unknown.…”
mentioning
confidence: 99%